2016
DOI: 10.1111/1365-2656.12528
|View full text |Cite
|
Sign up to set email alerts
|

Predator swamping reduces predation risk during nocturnal migration of juvenile salmon in a high‐mortality landscape

Abstract: Animal migrations are costly and are often characterized by high predation risk for individuals. Three of the most oft-assumed mechanisms for reducing risk for migrants are swamping predators with high densities, specific timing of migrations and increased body size. Assessing the relative importance of these mechanisms in reducing predation risk particularly for migrants is generally lacking due to the difficulties in tracking the fate of individuals and population-level characteristics simultaneously. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 68 publications
(163 reference statements)
5
92
0
Order By: Relevance
“…Nocturnal releases could reduce foraging efficiency of visual-based predators near release sites and give fish more time to disperse downstream (Furey, Hinch, Bass, et al, 2016;Ruggerone & Rogers, 1983). First, studies assessing seasonal consumption of hatchery prey by predators need to account for short-term, intensive predator feeding that could bias consumption and loss estimates if sampling missed such a behavioural event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nocturnal releases could reduce foraging efficiency of visual-based predators near release sites and give fish more time to disperse downstream (Furey, Hinch, Bass, et al, 2016;Ruggerone & Rogers, 1983). First, studies assessing seasonal consumption of hatchery prey by predators need to account for short-term, intensive predator feeding that could bias consumption and loss estimates if sampling missed such a behavioural event.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal and spatial variability among releases and release locations, as found in this study, illustrates the importance of making evaluations on a per-release basis. Thus, releasing all hatchery fish on one day, if possible, instead of every other day as occurred at Hells Canyon Dam, could potentially reduce predation by swamping predators with prey (Fritts & Pearsons, 2008;Furey, Hinch, Bass, et al, 2016). Nocturnal releases could reduce foraging efficiency of visual-based predators near release sites and give fish more time to disperse downstream (Furey, Hinch, Bass, et al, 2016;Ruggerone & Rogers, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…That strategy is supported by studies in freshwater, where juvenile salmon have been shown to survive better when migrating in large numbers, satiating place‐based predators (Furey et al. ). However, filter‐feeding baleen whales, like humpback whales, rely on dense aggregations of prey to forage efficiently (Piatt and Methven ; Deméré et al.…”
Section: Discussionmentioning
confidence: 88%
“…Numerical responses by avian (mergansers, Mergus merganser) and piscivorous fish species (spiny dogfish, Squalus suckleyi) have been documented in the Salish Sea in response to high densities of hatchery salmonids (Wood 1987, Beamish et al 1992. Alternatively, high densities of migrating juvenile salmonids have been shown to produce predator swamping effects, which result in lower mortality rates (Furey et al 2016). Alternatively, high densities of migrating juvenile salmonids have been shown to produce predator swamping effects, which result in lower mortality rates (Furey et al 2016).…”
Section: Discussionmentioning
confidence: 99%